Hypercalciuria in Postmenopausal Osteoporosis - Ayfer Kanberoğlu; Şule Tütün; Hale Aral; Güvenç Güvenen (Galenos Yayinevi, 2004)
Women aged between 35 to 75, termed as postmenopausal at least for one year, not smoking and not drinking alcohol, not using any medicine related with menopause and osteoporosis made up our patient and control groups. We investigated serum calcium, phosphorus, alkaline phosphatase, creatinine levels and urinary calcium level, calcium to creatinine ratio in post-menopausal women with osteoporosis (n = 25) and without osteoporosis (n =25). In our study hypercalciuria was found in 68% of women with osteoporosis and in 36% of women without osteoporosis. It was also found that there was a significant difference in calcium to creatinine ratio between the two groups (p<0,05). We also found that serum phosphorus level in women with osteoporosis was significantly higher than the other group (p<0,05). The results were compared with similar studies in literature.